Do ensinar como prática de flanagem ou perambulação - Sato, Eliana Satie (2014)
This essay has been conceived and written in order to question the atrophy of communication in the educational environment; the realization that social changes in the superstructure of capitalist production have produced a sort of paralysis in contemporary forms of communication was the starting point for this writing; the appeal of this text is due to the changes in the information and communication systems and their implications on the role of contemporary education; it is also legible as a plea in favor of possibilities to rethink the limits and potentialities of the encounter in the educational environment; and, finally, it conceives the teaching-learning process as flânerie or wandering practices. It dwells on the problem of the modes of human sense perception perceptiveness of oneself, the other, and the world - in the educational context within Walter Benjamin‟s thoughts. In so doing, Flânerie operates as a central concept, conceived both as a metaphor for thinking a new way of understanding the teaching-learning process as well as a methodological tool for research in education. Thus, this essay proposes a literature review by bringing to bear a discussion on a supposed contemporary symbolic blindness, especially in the educational environment, which is supposedly at the very core of the problem of the human contact; it should also be thought of as an attempt to amplify the understanding of Walter Benjamin‟s writings on teaching-learning process in industrial societies.